IoT-Based Ambulatory Vital Signs Data Transfer System - Misbahuddin, Syed; Zubairi, Junaid Ahmed; Alahdal, Abdul Rahman; Malik, Muhammad Arshad (Journal of Computer Networks and Communications, 2018)
In emergencies or life-threatening situations, patients are generally shifted to hospitals in ambulances. The health conditions of on-board patients can become critical if they are not evaluated and treated in time. Chances of saving lives can increase significantly if patients’ vital signs inside an ambulance or on-site triage area are transferred to a hospital in real time. If the ambulances are linked to target hospitals, then the physicians in emergency rooms can monitor on-board patients’ vital signs and issue instructions to paramedics to stabilize patients’ medical conditions before they reach the assigned hospitals. Transferred vital signs data may also be archived for medical records. The Internet of things (IoT) is a paradigm which envisions Internet connectivity of virtually everything on the earth. In this paper, an IoT-based low-cost solution is proposed to monitor, archive, analyze, and tag the vital signs data of multiple patients and transfer them to the remote hospital in real time. This opens up a lot of possibilities in telemedicine and disaster management. As a proof of concept, the functionality of the proposed system was validated by developing a prototype model utilizing an IoT-enabled medical sensor board and a Linux server mimicking the remote hospital server. Results of actual data transmission obtained during experimentation are also provided. It is hoped that the proposed system can play a role in saving human lives in disaster situations.